2018
DOI: 10.1126/science.aam9309
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of population-scale family trees with millions of relatives

Abstract: Family trees have vast applications in fields as diverse as genetics, anthropology, and economics. However, the collection of extended family trees is tedious and usually relies on resources with limited geographical scope and complex data usage restrictions. We collected 86 million profiles from publicly available online data shared by genealogy enthusiasts. After extensive cleaning and validation, we obtained population-scale family trees, including a single pedigree of 13 million individuals. We leveraged t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(146 citation statements)
references
References 76 publications
4
125
1
3
Order By: Relevance
“…Although lifespan is not very heritable in the population at large 3 recent studies have been able to identify 30,31 and replicate 46 some lifespan associated alleles that lower the risk of age related diseases. Our results imply that to find loci that promote survival to the highest ages in the population, genetic studies should be based on long lived cases including at least parental mortality information but preferably also mortality information of siblings and other first and second degree family members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although lifespan is not very heritable in the population at large 3 recent studies have been able to identify 30,31 and replicate 46 some lifespan associated alleles that lower the risk of age related diseases. Our results imply that to find loci that promote survival to the highest ages in the population, genetic studies should be based on long lived cases including at least parental mortality information but preferably also mortality information of siblings and other first and second degree family members.…”
Section: Discussionmentioning
confidence: 99%
“…Human lifespan has a low heritability (12-25%) 13 , whereas survival into extreme ages (longevity) clusters within families 48 . Studies showed that parents, siblings 46,811 , and children 6, 1216 of longevous persons lived longer than first degree relatives of non-longevous persons or population controls.…”
Section: Mainmentioning
confidence: 99%
“…Other software packages such as LDAK (Speed, Hemani, Johnson, & Balding, ) and GEMMA (Zhou & Stephens, ) also use REML. Very recently an analysis was published on huge human pedigrees and again the authors used REML (Kaplanis et al, ). Most use the average information algorithm developed by Robin and colleagues (Gilmour, Thompson, & Cullis, ).…”
Section: Snp Heritability and Remlmentioning
confidence: 99%
“…Genealogical records can reflect social and cultural structures, and record the flow of genetic material throughout history. In recent years, very large pedigree records have come into existence, owing to collaborative digitization of large genealogical records [1,2] and to digitization of large cohorts collected by healthcare providers, spanning up to millions of individuals [3][4][5][6][7]. Such population-scale pedigrees allow investigating the sociological and epidemiological history of human populations on a scale that is orders of magnitude larger than existing studies.…”
Section: Introductionmentioning
confidence: 99%